The Co-creative Meeting Practicing Consensual Effectivity in Organizations - Mandl, Christoph; Hauser, Markus; Mandl, Hanna; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
(3z(BCo-creative meetings(3y (Bfoster invention and innovation, and therefore enable innovative developmental processes in an organizational and inter-organizational context, including strategy development, product development, human resource development, R&D, and trans-organizational projects. This book illustrates the difference between productive and innovative organizations and what that difference means for meetings taking place in such organizations, both from a conceptual and practical point of view. It provides managers, coaches, consultants and other professionals whose job it is to organize meetings with clear and action-oriented guidelines for the design of (3z(Bco-creative meetings(3y(B, and also shows how to incorporate them through experiential learning.s
Foreword -- 1 Introduction -- 2 What is a Co-creative Meeting? -- 3 Dysfunctional Meeting Culture -- 4 Interdependency of Meetings and Organizations -- 5 Maxims of the Co-creative Meeting -- 6 Phases and Roles -- 7 Designing for Co-creativity -- 8 Institutionalizing Co-creative Meetings -- 9 Structural Variations for Co-creative Meetings -- 10 Consensual Efficiency -- Index.
Keywords: Economics; Industrial management; Entrepreneurship; Economics/Management Science; Management/Business for Professionals; Innovation/Technology Management; Entrepreneurship; Business Strategy/Leadership.; Non-Profit Enterprises/Corporate Social Responsibility